IDIOPATHIC THROMBOCYTOPENIA. WORK EXPERIENCE FOR 9 YEARS. AN EXAMPLE OF A CLINICAL CASE - Анастасия Владимировна Миронова; Юлия Олеговна Рождественская; Ирина Владимировна Болгова; Яна Вячеславовна Юнкина; Светлана Ивановна Елгина; Елена Владимировна Рудаева; Кира Борисовна Мозес; Яэль Центер; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2024)
Thrombocytopenia is a pathological condition characterized by a decrease in the number of platelets below 100 × 109/l. There are primary and secondary thrombocytopenia. However, the severity of thrombocytopenia is determined not by the number of platelets, but by the severity of hemorrhagic syndrome, which is manifested by the occurrence of petechiae, ecchymoses and bleeding from the microcirculatory bed. The article presents a retrospective analysis of the case histories of 128 patients with thrombocytopenia who were treated at the Kuzbass Clinical Hospital named after S.V. Belyaev for 9 years. With dynamic monitoring, timely medical care and adequate therapy, the prognosis for the life and health of patients with ITP is favorable.